Shared Tastes: Similarity in Aristotelian Character Friendship - Purdy, Ashley (Phronesis, 2025)
Aristotle claims that character friends are similar to each other. How should we understand this similarity, and what role does it play in friendship? In the paper, I argue that a broad similarity of ‘tastes’—which I understand as the appreciation of relatively good ends—is at least a facilitating condition on the formation of character friendship. This is because it (i) facilitates seeing the other as good in the first place, which is essential to character friendship; and (ii) enables the friends to spend time and share in activities together, which is characteristic of character friendship.